Solving three-dimensional Volterra integral equation by the reduced differential transform method - Ziqan, Abdelhalim; Armiti, Sawsan; Suwan, Iyad (International Journal of Applied Mathematical Research, 2016)
In this article, the results of two-dimensional reduced differential transform method is extended to three-dimensional case for solving three dimensional Volterra integral equation. Using the described method, the exact solution can be obtained after a few number of iterations. Moreover, examples on both linear and nonlinear Volterra integral equation are carried out to illustrate the efficiency and the accuracy of the presented method.